The risk and protective factors for entering organized crime groups and their association with different entering mechanisms: a systematic review using ASReview - Adamse, Ida (European journal of criminology, 2024)
The aims of the current systematic review are to provide an overview of the available evidence concerning the risk and protective factors for entering organized crime groups (OCGs), to explore which entry mechanisms for entering OCGs are distinguished in the literature, and to assess whether different sets of risk and protective factors could be identified for each of these entry mechanisms. To achieve these aims, a systematic literature search for qualitative, quantitative, and mixed method studies was performed up to 19 April 2021. To be included in the current review, studies had to be of empirical nature and published in either English or Dutch. ASReview was used to facilitate the inclusion process, a reference check of the included studies was performed, and all included studies in prior reviews on this topic were checked for inclusion. This process resulted in 51 included studies. Relevant study and sample characteristics, information on risk and protective factors, and indicated entry mechanisms were derived from the included studies. In line with earlier reviews, we find relatively strong evidence that being male, belonging to an ethnic minority group, committing certain crimes prior to entry at a young(er) age, committing multiple offenses without being specialized, and having a criminally involved family and/or friends are risk factors for entering OCGs. Entering OCGs occurs via four different entry mechanisms: active recruitment, soliciting for membership, growing into and self-setup. Based on the included studies, the risk and protective factors for entering OCGs that are associated with these different entry mechanisms into OCGs seem to overlap. Although the current review provides grounds to suggest that, in addition to a general set of risk and protective factors for entering OCGs, there might be different risk and protective factors associated with different entry mechanisms, longitudinal prospective studies are needed to substantiate this suggestion.